Rolling Bearing Fault Detection in the Range of Ultrasound - Goran Šiniković; Nenad Gubeljak; Emil Veg; Mladen Regodić; Darko Jagarinec; Ivana Medojević; Zorana Jeli (Tehnički Vjesnik, 2023)
Acoustic signals have been used widely to detect the integrity of metal parts and the soundness of their contact. Diverse methods are developed to evaluate the actual quality of metal-to-metal contact having a lubricating layer. These methods are sensitive to the sound waves resulting from the sliding and rolling contact of the adjacent items. The ongoing research and operational experience created an effective and reliable method for acoustic detection of rolling bearing damage. Sound waves are detected by an appropriate transducer (sensor). The signal is processed, and the resulting root-mean-square (RMS) voltage is tracked. An increase in the voltage level indicates deterioration in bearing conditions. In practice, however, such an application almost always involves several considerations, including a significant amount of interfering background noises, unacceptable sound wave attenuations, and inaccessibility of the desired sensor locations.